Analysis of Retransmission Policies for Parallel Data Transmission - Halepoto, I. A.; Sadhayo, I. H.; Memon, M. S.; Manzoor, A.; Bhatti, S. (Engineering, Technology & Applied Science Research, 2018)
Stream control transmission protocol (SCTP) is a transport layer protocol, which is efficient, reliable, and connection-oriented as compared to transmission control protocol (TCP) and user datagram protocol (UDP). Additionally, SCTP has more innovative features like multihoming, multistreaming and unordered delivery. With multihoming, SCTP establishes multiple paths between a sender and receiver. However, it only uses the primary path for data transmission and the secondary path (or paths) for fault tolerance. Concurrent multipath transfer extension of SCTP (CMT-SCTP) allows a sender to transmit data in parallel over multiple paths, which increases the overall transmission throughput. Parallel data transmission is beneficial for higher data rates. Parallel transmission or connection is also good in services such as video streaming where if one connection is occupied with errors the transmission continues on alternate links. With parallel transmission, the unordered data packets arrival is very common at receiver. The receiver has to wait until the missing data packets arrive, causing performance degradation while using CMT-SCTP. In order to reduce the transmission delay at the receiver, CMT-SCTP uses intelligent retransmission polices to immediately retransmit the missing packets. The retransmission policies used by CMT-SCTP are RTX-SSTHRESH, RTX-LOSSRATE and RTX-CWND. The main objective of this paper is the performance analysis of the retransmission policies. This paper evaluates RTX-SSTHRESH, RTX-LOSSRATE and RTX-CWND. Simulations are performed on the Network Simulator 2. In the simulations with various scenarios and parameters, it is observed that the RTX-LOSSRATE is a suitable policy.